Body dissatisfaction and smartphone addiction: the mediation role of intrusive imagery and fear of negative evaluation - Liu, Shiyu; Hu, Wen; Yang, Yingkai; Yang, Fahui (Frontiers in Psychology, 2023)
This research aimed to examine the mediating effect of intrusive imagery and fear of negative evaluation on the connection between body dissatisfaction and smartphone addiction. 5,909 participants were included in the research, with 53.8% of the sample being female. The average age of the participants was 19.87 years, and their ages ranged from 18 to 32 years. All individuals who were recruited for the study successfully finished the Satisfaction and Dissatisfaction with Body Parts Scale, the Smartphone Addiction Scale, the Intrusive Imagery Scale, and the Fear of Negative Evaluation Scale. Mediational analysis indicated that, with age, gender and body mass index under control, body dissatisfaction was linked to smartphone addiction via (1) the mediating role of intrusive imagery, (2) the mediating role of fear of negative evaluation, and (3) the serial mediating role of intrusive imagery and fear of negative evaluation. Our study for the first time advanced our understanding that intrusive imagery and fear of negative evaluation could be serial mediators of the relationship between body dissatisfaction and smartphone addiction. However, the cross-sectional design prevented us from establishing causality between these variables, which could be better examined in future longitudinal studies.